1999
DOI: 10.1046/j.1365-2230.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of a topical combination of retinaldehyde 0.1% with erythromycin 4% in acne vulgaris

Abstract: The objective of this randomized, controlled, multicentre study was to assess the efficacy and safety of a topically applied retinaldehyde 0.1% gel in combination with a topical erythromycin 4% lotion for the treatment of acne vulgaris. Treatment consisted of applying either retinaldehyde or its vehicle every morning and erythromycin every evening for 8 weeks. Efficacy parameters were sequential lesion counts for papules and pustules, and a 6-point semiquantitative scale for comedones and microcysts. Safety pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…The number of acne lesions was reduced by between 49 and 62%. The comparison of tretinoin microsphere formulation demonstrated a similar efficacy but lower irritative potential of adapalene [30, 31, 32, 33]. …”
Section: Adapalenementioning
confidence: 99%
See 1 more Smart Citation
“…The number of acne lesions was reduced by between 49 and 62%. The comparison of tretinoin microsphere formulation demonstrated a similar efficacy but lower irritative potential of adapalene [30, 31, 32, 33]. …”
Section: Adapalenementioning
confidence: 99%
“…In both treatment groups, papules and pustules were reduced significantly. Local tolerance was very satisfactory [41]. …”
Section: Retinaldehyde and Retinyl-β-glucuronidementioning
confidence: 99%
“…Duell et al [9] suggested that topical ROL is a more efficient way to deliver RA in the skin than topical RA itself. Likewise, all-trans-retinaldehyde (RAL) is converted by epidermal cells to both storage (all-trans-retinyl esters) and active (RA) forms of vitamin A and exerts significant retinoid biological activities [5][6][7], with a very good local tolerance even at a concentration of 0.1% [10,11]. On the other hand, RAL showed comedolytic [12] and antibacterial activities [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of RAL have been demonstrated when used at 0.1% in combination with 4% erythromycin [9] or with glycolic acid (GA) in the treatment of mild to moderate acne [10]. Indeed, GA, an α-hydroxy acid (AHA), is known for its keratolytic properties [11,12,13] and its efficacy in reducing atrophic acne scars [14].…”
Section: Introductionmentioning
confidence: 99%